2017
DOI: 10.1182/bloodadvances.2017006726
|View full text |Cite
|
Sign up to set email alerts
|

Platelet dense granules begin to selectively accumulate mepacrine during proplatelet formation

Abstract: Platelet dense granules (DGs) are storage organelles for calcium ions, small organic molecules such as ADP and serotonin, and larger polyphosphates that are secreted upon platelet stimulation to enhance platelet activation, adhesion, and stabilization at sites of vascular damage. DGs are thought to fully mature within megakaryocytes (MKs) prior to platelet formation. Here we challenge this notion by exploiting vital fluorescent dyes to distinguish mildly acidic DGs from highly acidic compartments by microscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…Because empty or immature granules may not be identified by TEM, mepacrine uptake was quantified as a measure of DG amount. 36,37 Mepacrine uptake was decreased by 45% in resting DKO platelets compared with WT ( Figure 4B). As a control, we observed that thrombin preactivated platelets incorporated minor amount of mepacrine, irrespective of their genotype ( Figure 4B).…”
Section: Rab32 and Rab38 Are Required For Dense Granule Formationmentioning
confidence: 98%
“…Because empty or immature granules may not be identified by TEM, mepacrine uptake was quantified as a measure of DG amount. 36,37 Mepacrine uptake was decreased by 45% in resting DKO platelets compared with WT ( Figure 4B). As a control, we observed that thrombin preactivated platelets incorporated minor amount of mepacrine, irrespective of their genotype ( Figure 4B).…”
Section: Rab32 and Rab38 Are Required For Dense Granule Formationmentioning
confidence: 98%
“…Studies of these systems are likely to yield interesting surprises. For example, recent evidence suggests that dense granules do not mature until the final stages of platelet formation from megakaryocytes . Understanding the temporal regulation of this step will likely lead to new ideas regarding signaling pathways that can regulate LRO biogenesis in specific cell types.…”
Section: Perspectivesmentioning
confidence: 99%
“…Formation of platelet granules begins in megakaryocytes, but maturation continues in circulating platelets 12 , 13 . Human platelet granule deficiency syndromes, also referred to as storage pool disorders, and their related murine models have been a major source of study of platelet granulogenesis.…”
Section: Biogenesis Of Platelet Granulesmentioning
confidence: 99%
“…BLOC3 functions as a guanine nucleotide exchange factor for cell type-specific Rab GTPases, such as Rab32 and Rab38 in melanocytes 63 , 64 . A direct role of Rab32 and Rab38 in dense granule biogenesis in megakaryocytes has also been implicated 13 , 64 . RUNX1 mutations lead to dense granule but not α -granule deficiency due to dysregulation of Pallidin (HPS9) transcription 65 .…”
Section: Biogenesis Of Platelet Granulesmentioning
confidence: 99%